Pengaruh Merchandise, Promosi Dan Atmosphere Terhadap Keputusan Pembelian Miniso Kota Malang (Studi kasus Mahasiswa Universitas Islam Malang) - Samuriah, Samuriah; Khalikussabir, Khalikussabir; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The purpose of this study is to find out how the influence of Merchandise, Promotion, and Atmosphere on the purchase decision of Malang City Miniso. The data collection method uses purposive sampling, which is sampling from the population based on certain criteria. The data analysis technique used to measure the question indicators on the questionnaire is the Likert scale. In this study, the data source used is primary data using analysis tools and statistics of the IMB SPSS25 program. This study uses a data collection method with questionnaires and samples used in this study as many as 115 respondents. The data analysis method includes quantitative analysis using the multiple linear regression technique method as well as hypothesis tests simultaneously (F test) and passively (t test). The results of this study show that simultaneously Atmosphere, Promotion, and Atmosphere have a simultaneous influence on the purchase decision of Miniso products in Malang city at a significant level of 0.000<0.05. Then in parsian or individually, the variables of Merchandise, Promotion, and Atmosphere have a positive effect simultaneously on product purchase decisions at Miniso Malang City. Keywords: Merchandise, Promotion, and Atmosphere, Purchase Decision